PENGAWETAN KAYU SENGON MELALUI RENDAMAN DINGIN MENGGUNAKAN BAHAN PENGAWET ENBOR SP DITINJAU TERHADAP SIFAT MEKANIK - Pangestuti, Endah Kanti; Lashari, Lashari; Hardomo, Agus (Jurnal Teknik Sipil dan Perencanaan, 2016)
The use of wood in construction world continues to increase both for the use of structural and non-structural.Â  Needs a very large timber impact on the availability of wood shrinks every year as a result of exploitation by large scale. One attempt to extend the service life of wood is the wood preservation. This study aims to determine mechanical properties of wood by soaking sengon due to cold preservation with preservative EnborSP. The method used is the method of experiments carried out in the Laboratory of Materials of Civil Engineering, Faculty of Engineering, State University of Semarang. The preservation process used isa process with a cold soaking method, with a preservative solution EnborSP with a concentration of 0%, 3%, 6% and 9%. The response observed was the value-the value retention of preservatives, and mechanical properties (compressive strength of parallel fiber direction, flexural strength and surface hardness) of wood. Preservation method applied is cold soaking (for 5 days or 120 hours). Average retention value-average increase of 2.57kg/m3 (3%), 4.89kg/m3 (6%), and 6.74kg/m3 (9%). Value - average compressive strength of parallel to the direction of the wood fiber sengon increase of 149.39kg/cm2 (0%), 156.35kg/cm2 (3%), 187.80kg/cm2 (6%), and 216, 44kg/cm2 (9%). Value â average flexural strength sengon increase of 175.36kg/cm2 (0%), 202.55kg/cm2 (3%), 272.64kg/cm2 (6%), and 362.81kg/cm2 (9%). Value â average penetration sengon wood decreased from 0.93cm (0%), 0.67cm (3%), 0.57cm (6%), and 0.43cm (9%). This decrease shows that there is an increase in the value of the wood sengon surface hardness.Â Salah satu usaha untuk memperpanjang umur pemakaian kayu adalah dengan pengawetan kayu. Penelitian ini bertujuan untuk mengetahuiÂ sifat mekanik kayu sengon akibat pengawetan secara rendaman dingin dengan bahan pengawet Enbor SP. Metode penelitian yang digunakan adalah metode eksperimen yang dilakukan di Laboratorium BahanÂ dan Laboratorium Kerja KayuÂ Teknik Sipil Fakultas Teknik UniversitasÂ NegeriÂ Semarang.Â Proses pengawetan yang digunakan adalah proses dengan metode rendaman dingin, dengan larutan bahan pengawet Enbor SP dengan konsentrasi 0 %, 3 %, 6 %, dan 9 %. Respon yang diamati adalah nilai â nilai retensi bahan pengawet dan serta sifat mekanis (kuat tekan tekan sejajar arah serat, kuatÂ Â lentur dan kekerasan permukaan) kayu. Metode pengawetan yang diterapkan adalah rendaman dingin (selama 5 hari atau 120 jam). Nilai retensi rata â rata mengalami kenaikan dari 2,57 kg/m3Â (3 %), 4,89 kg/m3Â (6 %), dan 6,74 kg/m3Â (9 %). Nilai rata â rata kekuatan tekan sejajar arah serat kayu sengon mengalami kenaikan dariÂ 149,39 kg/cm2Â (0 %), 156,35 kg/cm2Â (3 %), 187,80 kg/cm2Â (6 %), dan 216,44 kg/cm2Â (9 %). Nilai rata â rata kekuatan lentur kayu sengon mengalami kenaikan dari 175,36 kg/cm2Â (0 %), 202,55 kg/cm2Â (3 %), 272,64 kg/cm2Â (6 %), dan 362,81 kg/cm2Â (9%).Â Nilai rata â rata penembusan kayu sengon menurun dari 0,93 cm (0 %), 0,67 cm (3 %), 0,57 cm (6 %), dan 0,43 cm (9 %). Penurunan ini memperlihatkan bahwa ada peningkatan nilai kekerasan permukaan kayu sengon.